Implementasi Ekstrakurikuler Keagamaan Dalam Pembentukan Karakter Religius Peserta Didik di SMP Islam Brawijaya Kota Mojokerto - Yulianti, Eva (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Indonesian education in recent decades gets many problems such as the weak young generations‟character because the success of a country can be seen from its people‟s characters. We need some breakthroughs which one of them can be done by implementing early religious character in school either in classroom and in religious exstracurricular. Religious exstracurricular has important role in the process of students‟ religious character buildings. This research is done in Brawijaya Islamic Junior Highschool, Mojokerto to know (1) The plan of religious extracurricular program in school, (2) The implementation of religious exstracurricular in building students‟ religious characters in school, and (3) Evaluation of the implementation of religious exstracurricular towards the building of students‟ religious characters in school.  This research uses qualitative research with case study approach. This research uses three data collection techniques; they are observation, interview and documentation. This research uses interactive data analysis by Miles and Huberman with stages of data collection, data presentation, data conclusion and data validation.  This results show that (1) The plan of religious extracurricular programs aims to build students‟ religious characters. The religious extracurricular program includes Qur’an arts literacy, Qur’an memoryzation, praying together, shalawat al-banjari, a spiritual tour, basic training of rohis leadership and commemoration of Islamic holidays. (2) The Implementation of religious extracurricular is done with three kinds of daily, weekly and anually activities. It is done by giving spiritual lecture, good example, and habit in the school‟s activities. (3) The evaluation of religious extracurricular implementation can be seen from how far the students‟ religious knowledge and attitude according to the learning results books of them. The effects of religious exstracurricular in Brawijaya Islamic Junior High School in positive, it means that this program can help students understand Islamic values and decrease teens‟ naughtiness and bad influence for the students.